1999
DOI: 10.1007/s004410051343
|View full text |Cite
|
Sign up to set email alerts
|

Localization of leech excitatory peptide, a member of the GGNG peptides, in the central nervous system of a leech ( Whitmania pigra ) by immunohistochemistry and in situ hybridization

Abstract: We have recently isolated a myoactive peptide, called leech excitatory peptide, belonging to the GGNG peptide family from two species of leeches, Hirudo nipponia and Whitmania pigra. Immunohistochemistry and in situ hybridization were employed to localize leech excitatory peptide-like peptide(s) and its gene expression in the central nervous system of W. pigra. A pair of neuronal somata were stained by both immunohistochemistry and in situ hybridization in the supraesophageal, subesophageal, and segmental gang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The extracts using different extracting methods showed different anticoagulant and anti-thrombotic activity (Ding et al, 1994). An active peptide, called leech excitatory peptide, has been isolated (Nagahama et al, 1999).…”
Section: Hirudomentioning
confidence: 99%
“…The extracts using different extracting methods showed different anticoagulant and anti-thrombotic activity (Ding et al, 1994). An active peptide, called leech excitatory peptide, has been isolated (Nagahama et al, 1999).…”
Section: Hirudomentioning
confidence: 99%
“…Comparative genomic approaches [19,20,40] and other studies identified multiple annelid pNPs and neuropeptides, including RFa [13,41-47], FVRIa [48-50], excitatory peptide (EP) [51-53], egg-laying hormone (ELH) [54], myomodulin [55-57], RGWa [13], L11 or elevenin [28], vasopressin [39,58,59], gonadotropin releasing hormone (GnRH) [60,61], insulin-related peptides [62], neuropeptide Y (NPY) [63,64] and myoinhibitory peptide (MIP) [65]. Despite these advances, a complete picture of annelid neuropeptide diversity is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Its expression in different larval or adult insects is connected to the digestive system (7,(18)(19)(20)(21)(22). Experiments with EP showed a myo-excitatory effect that included digestive tissues of oligochaetes (6), leeches (23,24), and a gastropod species (25), and association with digestive tissues was also shown by immunohistochemistry on a polychaete (26). (See also table 2 for functional and anatomical association of EP/CCHamides).…”
Section: Introductionmentioning
confidence: 93%
“…The behavioral effect of a single type of peptide on different animals has only been tested for FMRFamide and its orthologue FLRFamide and the different studies showed some species-specific effects in different trochozoan larvae (41,(43)(44)(45). The influence of EP on locomotion of L. longissimus larvae and the broad expression in the brain and prominent ventral nerve cord of the juveniles stands in contrast to the myo-excitatory effect of EPs in different adult/juvenile annelid (6,23,24,26) and mollusc (25) species and the repeated association of EPs and CCHamides with feeding or the digestive system in annelids (6,23,24,26,64), molluscs (25,65) and insects (5,7,(16)(17)(18)(19)(20)(21)(22)) (see also table 2). This suggests that the degree of functional conservation can vary depending on the type of peptide, the animal taxon or the developmental stages and that also functionally more conserved peptides like the EP/CCHamides can show plasticity in their behavioral association.…”
Section: Functional Association Of Peptides Can Vary During Evolutionmentioning
confidence: 99%